Origin, trophic transfer and recycling of particulate organic matter in two upwelling bays of Humboldt Current System: Insights from compound-specific isotopic compositions of amino acids. - Benjamín Srain; Edgart Flores; Jorge Valdés; Andrés Camaño (PLoS ONE)
The Chilean upwelling bays are highly productive ecosystems shaped by their interactions with the open ocean. Although significant knowledge exists regarding their hydrodynamic and ecological processes, the spatial dynamics of trophic transfer and heterotrophic resynthesis of organic matter remain insufficiently understood. To address these knowledge gaps, we conducted a compound-specific isotope analysis of amino acids (CSIAA) on suspended and sinking particulate organic matter from Mejillones and Antofagasta bays, two oceanographic environments characterized by contrasting hydrodynamic conditions and topographic orientations. In Mejillones Bay, the CSIAA trophic positions for metazoan (1.7 ± 0.5) and protozoan (2.3 ± 0.3) were significantly higher compared to those in Antofagasta Bay (metazoans: 1.3 ± 0.6; protozoans: 1.5 ± 0.3), highlighting protozoans as primary trophic vectors. MixSIAR analysis indicated that phytoplankton is a key source of particulate organic matter in both bays; however, Mejillones Bay exhibited a greater proportion of microbially degraded organic matter. Enhanced heterotrophic resynthesis in Mejillones Bay (ΣV: 1.9-2.5) was associated with lower oxygen levels, increased concentrations of NO₂ ⁻ , and heightened stratification of the water column. Additionally, depth-dependent variations in δ15N for phenylalanine and threonine indicated a greater solubilization of particles, which contributed to a reduction in the export of particulate organic matter (averaging 9 ± 2 mg C/m²/d). These findings underscore the critical role of the intricate interactions between the bay's topographic features and the physical and biological processes that ultimately influence the cycling trajectories of particulate organic matter in upwelling bays.